Technical meeting on Ethiopian National Framework for Climate Services (NFCS) - Teshome, Asaminew; Tesfaye, Kindie; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The National Framework for Climate Services (NFCS), which is part of the Global Framework for Climate Services (GFCS), is a coordinating mechanism that enables the development and delivery of climate services at the national level. GFCS was established in 2009, through a high-level declaration at the 3rd World Climate Conference organized by the World Meteorological Organization (WMO), other United Nations (UN) agencies, governments and partners to guide the development of climate services around the world. The main reason for establishing GFCS was the ever-increasing frequency and intensity of hydrometeorological hazards, vulnerability, exposure to those hazards, and limited capacity to cope. The vision of the GFCS is to enable society to better manage the risks and opportunities arising from climate variability and change, especially for those who are most vulnerable to such risks. This will be achieved through the development and incorporation of science-based climate information and prediction into planning, policy and practice.